Endovascular Management of Acute Superior Mesenteric Artery Thrombosis in a Delayed Setting - Agamya Saxena; Prashant Srivastava (International Journal of Medical Research and Review, 2019)
Acute mesenteric ischemia [AMI] is a life-threatening situation, the diagnosis of which is often missed in early stages. Late diagnosis often precludes endovascular management as the primary treatment. The authors here present a case of seven days history of acute mesenteric ischemia in a young female, who not just benefited from endovascular management, but also a major surgical intervention was avoided andwas discharged from the hospital uneventfully. The decision to consider a patient for endovascular management in a late stage, requires a good interdisciplinary communication and successful outcome in such a scenario is rarely achieved.